A diaphragm material and its preparation process
By using a combination of multi-layer structure and nano-toughening layer in the TPU film, the problem of plastic deformation at high temperatures and brittleness at low temperatures is solved, the hardness and temperature resistance of the material are improved, and the authenticity of the sound is ensured. and product stability.
Patent Information
- Application Number
- CN202210977559.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-15
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-08-15
AI Technical Summary
Existing TPU films are prone to plastic deformation at high temperatures, become brittle at low temperatures, and have poor elasticity, resulting in sound distortion and unstable quality.
The diaphragm material structure consisting of a release layer, a first thermoplastic elastomer layer, a nano-toughening layer and a second thermoplastic elastomer layer are adopted, and the hardness and resistance of the material are prepared by coating process and heating forming method. Temperature performance.
The hardness, high and low temperature resistance, impact resistance and fatigue life of the diaphragm material are improved, ensuring the authenticity of sound and product stability.
Smart Images

Figure SMS_1 
Figure HDA0003798956990000011
Abstract
Description
Technical Field
[0001] The present invention relates to the field of preparation of polyurethane diaphragms, B32B27 / 40, and in particular to a diaphragm material and a preparation process thereof. Background Art
[0002] TPU (polyurethane thermoplastic elastomer) film has excellent wear resistance, good tensile strength and elongation, as well as good low temperature resistance and weather resistance. It is widely used in the production of diaphragm materials in the field of electroacoustics. At present, the production process of TPU film on the market mainly adopts calendering, casting, film blowing and other processes. The TPU film products prepared by calendering are thicker and less uniform, and are not suitable for thin products; the TPU film prepared by casting has poor tear resistance; the TPU film prepared by film blowing has poor thickness uniformity and many crystal points. The solvent coating method can generally produce products with uniform thickness of 5-40μm, excellent appearance and stable quality, but TPU film with a thickness of 50-200μm will have problems such as poor drying and holes when prepared by coating method. At the same time, due to its own limitations, TPU material has poor heat resistance and cold resistance, is prone to plastic deformation at high temperature, becomes brittle and destroyed at low temperature, and has poor elasticity, large tensile permanent change, and low internal friction, which makes the distortion high, and cannot completely restore the essence of sound.
[0003] The patent with application number 201710153352.4 discloses a continuous coating production system and method for TPU film. The continuous coating production system and method for TPU film include a first unwinding unit to unwind the film body; a lead-in unit, a first peeling unit, a coating unit, a drying unit, and a UV curing unit. The present invention abandons the traditional roll-to-roll connection method of the material to be coated, avoiding the shortcomings of interlayer materials being difficult to connect and difficult to bond firmly. By adding an intermediate carrier film as a lead-in film, it speeds up production efficiency, improves joint strength, and avoids the TPU film being heated in the oven to improve product quality.
[0004] A loudspeaker diaphragm is disclosed in the patent application number 201510600106.X. The present invention discloses a loudspeaker diaphragm, comprising a dome portion (20) at the center and a folding ring portion (10) at the edge, wherein the folding ring portion (10) is a single-layer structure composed of a layer of thermoplastic polyester elastomer TPEE material layer (2); or, the folding ring portion (10) is a composite structure composed of at least one layer of thermoplastic polyester elastomer TPEE material layer (2). Compared with a diaphragm made of TPU material, the loudspeaker diaphragm of the present invention not only has good toughness and strength, can effectively reduce the resonant frequency of the product and widen the product frequency band, but also has excellent structural stability, high power resistance reliability and high resonant frequency stability. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present invention provides a diaphragm material, which comprises, from top to bottom, a release layer, a first thermoplastic elastomer layer, a nano-toughening layer, and a second thermoplastic elastomer layer.
[0006] In some preferred embodiments, the material of the release layer is selected from one of polyethylene terephthalate (PET), co-extruded oriented polypropylene (OPP) film, biaxially oriented polypropylene (BOPP) film, cast polypropylene (CPP) film, and release paper; preferably, the material of the release layer is OPP film and / or CPP film.
[0007] In some preferred embodiments, the tensile strength of the OPP film is 50-95 MPa; preferably, the tensile strength of the OPP film is 55-89 MPa.
[0008] In some preferred embodiments, the peel force of the CPP film is 1-100g / 25mm, the longitudinal tensile strength MD is ≥20MPa, the transverse tensile strength TD is ≥15MPa, and the elongation at break is ≥80%; preferably, the peel force of the CPP film is 50g / 25mm, the longitudinal tensile strength MD is ≥25MPa, the transverse tensile strength TD is ≥20MPa, and the elongation at break is ≥88%.
[0009] In some preferred embodiments, the thickness of the release layer is 10-200 μm; preferably, the thickness of the release layer is 40-100 μm; further preferably, the thickness of the release layer is 80 μm.
[0010] In some preferred embodiments, the thermoplastic elastomer in the first thermoplastic elastomer layer is selected from one or more of polyester thermoplastic elastomers, polyamide thermoplastic elastomers, polyurethane thermoplastic elastomers, thermoplastic silicone elastomers, styrene / butadiene / styrene block copolymers, and styrene / isoprene / styrene block copolymers; preferably, the thermoplastic elastomer in the first thermoplastic elastomer layer is a polyurethane thermoplastic elastomer.
[0011] In some preferred embodiments, the polyurethane thermoplastic elastomer is selected from one or more of polyurethane elastomer particles, water-based polyurethane resin, and oily polyurethane resin; preferably, the polyurethane thermoplastic elastomer is an oily polyurethane resin.
[0012] In some preferred embodiments, the 100% modulus of the oily polyurethane resin is 5-15 MPa, the tensile strength is 30-60 MPa, and the elongation is 450-700%; preferably, the 100% modulus of the oily polyurethane resin is 8.0 MPa, the tensile strength is 55.0 MPa, and the elongation is 500%.
[0013] In some preferred embodiments, the coating thickness of the first thermoplastic elastomer layer is 5-75 μm; preferably, the coating thickness of the first thermoplastic elastomer layer is 5-50 μm; further preferably, the coating thickness of the first thermoplastic elastomer layer is 15 μm.
[0014] The addition of thermoplastic elastomer can improve the wear resistance, tensile properties and tensile strength of the diaphragm, but its high and low temperature stability is poor. The applicant has found that the addition of oily polyurethane resin to the above system has a thermoplastic linear structure, and the solid body formed is strong and has good anti-permeability, which can effectively increase the hardness of the diaphragm. In particular, the oily polyurethane resin with a 100% modulus of 5-15MPa, a tensile strength of 30-70MPa, and an elongation of 400-700% is selected. It synergizes with the toughening layer nanofiber membrane and the release film in the system, and the adhesion between different layer structures is strong. It can be formed by heating and bonding with the toughening layer, and at the same time further improves the diaphragm material, which is easy to undergo plastic deformation at high temperature, brittle at low temperature, poor elasticity, large tensile permanent deformation, and high distortion. The hardness of the resulting diaphragm reaches 65-95A and the gloss is high.
[0015] In some preferred embodiments, the material of the second thermoplastic elastomer layer is the same as the material of the second thermoplastic elastomer layer.
[0016] In some preferred embodiments, the coating thickness of the first thermoplastic elastomer layer is 5-75 μm; preferably, the coating thickness of the first thermoplastic elastomer layer is 5-50 μm; further preferably, the coating thickness of the first thermoplastic elastomer layer is 15 μm.
[0017] In some preferred embodiments, the nano-toughened layer is obtained by preparing a nanofiber membrane using a thermoplastic polymer by an electrospinning process.
[0018] In some preferred embodiments, the thermoplastic polymer is selected from one or more of polyimide, polyamide, polycaprolactone, polyethersulfone, polyetherketone, polyolefin, and polyphenylene ether; preferably, the thermoplastic polymer is polyamide; further preferably, the thermoplastic polymer is PA66.
[0019] In some preferred embodiments, the thickness of the nano-toughening layer is 5-40 μm; preferably, the thickness of the nano-toughening layer is 5-30 μm; further preferably, the thickness of the nano-toughening layer is 7 μm.
[0020] A second aspect of the present invention provides a process for preparing a diaphragm material, which comprises the following steps:
[0021] (1) dissolving the thermoplastic elastomer in the first thermoplastic elastomer layer in an organic solvent, stirring and filtering, and then adding isocyanate and continuing to stir and dissolve to obtain a raw material composition for the first thermoplastic elastomer layer;
[0022] (2) coating the raw material composition of the first thermoplastic elastomer layer obtained in (1) on the release layer and placing it in an oven to dry; then heating and laminating it with the nano-toughening layer, peeling off the nanofiber membrane base film material and rolling it up from the back;
[0023] (3) The raw material composition of the first thermoplastic elastomer layer obtained in (1) is applied to the release layer and placed in an oven for drying; then, the release layer is heated and laminated with the film obtained in (2), and the OPP film material of the composite film obtained in (2) is peeled off and rolled up from the back.
[0024] (4) The film obtained in (3) is placed under a certain temperature and humidity for curing.
[0025] In step (1)
[0026] In some preferred embodiments, the organic solvent is selected from one or more of N,N-dimethylformamide, ethyl acetate, hexafluoroisopropanol, toluene, butanone, cyclohexanone, and tetrahydrofuran; preferably, the organic solvent is butanone.
[0027] In some preferred embodiments, the weight ratio of the thermoplastic elastomer to the organic solvent in the first thermoplastic elastomer layer is 1:(1.5~7); preferably, the weight ratio of the material of the first thermoplastic elastomer layer to the organic solvent is 1:(2~6); further preferably, the weight ratio of the thermoplastic elastomer to the organic solvent in the first thermoplastic elastomer layer is 1:4.2.
[0028] In some preferred embodiments, the solid content of the thermoplastic elastomer after filtration is 7-55wt%; preferably, the solid content of the thermoplastic elastomer after filtration is 10-50wt%; further preferably, the solid content of the thermoplastic elastomer after filtration is 20-30wt%; further preferably, the solid content of the thermoplastic elastomer after filtration is 26wt%.
[0029] In some preferred embodiments, the isocyanate is selected from one or more of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, and hexamethylene diisocyanate; preferably, the isocyanate is toluene diisocyanate.
[0030] In some preferred embodiments, the solid content of the toluene diisocyanate is 70-80 wt %; preferably, the solid content of the toluene diisocyanate is 75 wt %.
[0031] In some preferred embodiments, the weight ratio of the isocyanate to the total weight of the thermoplastic elastomer and the organic solvent is 1:(0.02-0.01); preferably, the weight ratio of the isocyanate to the total weight of the thermoplastic elastomer and the organic solvent is 1:(0.02-0.08); further preferably, the weight ratio of the isocyanate to the total weight of the thermoplastic elastomer and the organic solvent is 1:0.05.
[0032] In steps (2) and (3)
[0033] In some preferred embodiments, the coating method is selected from one of blade coating, roller coating, brush coating, spray coating, and cationic electrodeposition (CED); preferably, the coating method is blade coating.
[0034] In some preferred embodiments, the coating speed is 5-25 m / min; preferably, the coating speed is 5-20 m / min; further preferably, the coating speed is 15 m / min.
[0035] In some preferred embodiments, the temperature of the oven is set to a gradient temperature increase. Preferably, the gradient temperature of the oven is set to: 50-65°C for 1-2 min; 65-80°C for 1-2 min; 80-95°C for 1-2 min; 95-105°C for 1-2 min; 105-115°C for 1-2 min; 80-90°C for 1-2 min; 55-65°C for 1-2 min; further preferably, the gradient temperature of the oven is set to: 60°C for 1.87 min; 70°C for 1.87 min; 90°C for 1.87 min; 100°C for 1.87 min; 110°C for 1.87 min; 95°C for 1.87 min; 60°C for 1.87 min. In the present application, by controlling the coating speed and subjecting the obtained film to programmed heating and drying, the reaction between the thermoplastic polyurethane elastomer and the isocyanate can be promoted to be complete, the self-polymerization reaction of the isocyanate can be avoided to a large extent, and the drying of the thermoplastic elastomer layer coating can be accelerated, so that the prepared TPU film has the advantages of uniform thickness, excellent appearance and stable performance. At the same time, coating it on the composite nanofiber membrane toughening layer not only improves the high and low temperature resistance of the diaphragm material, but also improves the impact resistance and fatigue life of the diaphragm material.
[0036] In step (4),
[0037] In some preferred embodiments, the temperature is 40-50°C, the humidity is 5-20%, and the time is 2-4 days; preferably, the temperature is 45°C, the humidity is 10%, and the time is 3 days.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The diaphragm of the present invention comprises, from top to bottom, a release layer, a first thermoplastic elastomer layer, a nano-toughening layer, and a second thermoplastic elastomer layer. Diaphragm materials of different thicknesses, different hardnesses, and different moduli are prepared by composite nanofiber membranes with two layers of thermoplastic polyurethane films. The obtained diaphragm has uniform thickness of 10-50 μm, hardness of 65-95 A, stable modulus and glossiness, and excellent appearance. At the same time, the composite nanofiber membrane not only improves the high and low temperature resistance of the diaphragm material, but also improves the elastic properties and tensile strength, and also improves the impact resistance and fatigue life of the diaphragm material.
[0040] (2) In the present invention, the thermoplastic elastomer material is coated on the release layer by coating, and then the diaphragm material is prepared with the toughening layer by heating and molding. The thickness is adjustable, the production process is simple, the product yield is high, and the operation is convenient. The electroacoustic manufacturer only needs to make the diaphragm according to the molding conditions without the need for compounding adhesive film or PEEK and other materials, which can effectively improve efficiency and save costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Schematic diagram of the diaphragm obtained in Example 1. DETAILED DESCRIPTION
[0042] Example 1
[0043] 1. A diaphragm material, comprising, from top to bottom, a release layer, a first thermoplastic elastomer layer, a nano-toughening layer, and a second thermoplastic elastomer layer, such as Figure 1 shown.
[0044] The release layer is made of OPP film.
[0045] The OPP film has a tensile strength of 55-89 MPa (purchased from Suzhou Kunling Film Industry Co., Ltd., model STC50N).
[0046] The thickness of the release layer is 80 μm.
[0047] The thermoplastic elastomer in the first thermoplastic elastomer layer is polyurethane thermoplastic elastomer.
[0048] The thermoplastic elastomer in the first thermoplastic elastomer layer is a polyurethane thermoplastic elastomer; and the polyurethane thermoplastic elastomer is an oily polyurethane resin.
[0049] The 100% modulus of the oily polyurethane resin is 8.0 MPa, the tensile strength is 55.0 MPa, and the elongation is 50% (purchased from Yantai Huada Chemical, model number HD-80NG).
[0050] The coating thickness of the first thermoplastic elastomer layer was 15 μm.
[0051] The specific implementation manner of the preparation method of the second thermoplastic elastomer layer is the same as that of the first thermoplastic elastomer layer.
[0052] The coating thickness of the second thermoplastic elastomer layer was 15 μm.
[0053] The nano toughening layer is obtained by preparing a nano fiber membrane by using a thermoplastic polymer through an electrostatic spinning process.
[0054] The thermoplastic polymer is polyamide; the thermoplastic polymer is PA66 (New Zealand Revolution Fibres Company, model number is Xantu.Layr).
[0055] The thickness of the nano toughening layer is 7 μm.
[0056] 2. A process for preparing a diaphragm material, comprising the following steps:
[0057] (1) dissolving the thermoplastic elastomer in the first thermoplastic elastomer layer in an organic solvent, stirring and filtering, and then adding isocyanate and continuing to stir and dissolve to obtain a raw material composition for the first thermoplastic elastomer layer;
[0058] (2) coating the raw material composition of the first thermoplastic elastomer layer obtained in (1) on the release layer and placing it in an oven to dry; then heating and laminating it with the nano-toughening layer, peeling off the nanofiber membrane base film material and rolling it up from the back;
[0059] (3) coating the raw material composition of the first thermoplastic elastomer layer obtained in (1) on the release layer and placing it in an oven to dry; then heating and laminating it with the film obtained in (2), and peeling off the OPP film material of the composite film obtained in (2) and rolling it up from the back;
[0060] (4) The film obtained in (3) is placed under a certain temperature and humidity for curing.
[0061] In step (1)
[0062] The organic solvent is butanone.
[0063] The weight ratio of the thermoplastic elastomer to the organic solvent is 1:4.2.
[0064] The solid content of the filtered thermoplastic elastomer is 26 wt %.
[0065] The isocyanate is toluene diisocyanate.
[0066] The solid content of the toluene diisocyanate is 75wt% (purchased from Covestro L-75 curing agent)
[0067] The weight ratio of the isocyanate to the total weight of the thermoplastic elastomer and the organic solvent is 1:0.05.
[0068] In steps (2) and (3)
[0069] The coating method is knife coating.
[0070] The coating speed is 15 m / min.
[0071] The temperature of the oven is set to increase gradually.
[0072] The gradient temperature of the oven was set as follows: 60° C. for 1.87 min; 70° C. for 1.87 min; 90° C. for 1.87 min; 100° C. for 1.87 min; 110° C. for 1.87 min; 95° C. for 1.87 min; and 60° C. for 1.87 min.
[0073] In step (4),
[0074] The temperature is 45° C., the humidity is 10%, and the time is 3 days.
[0075] Example 2
[0076] 1. A diaphragm material, which is different from that of embodiment 1 in that:
[0077] The material of the release layer is CPP film.
[0078] The CPP film has a peel force of 50g / 25mm, a longitudinal tensile strength MD of ≥25MPa, a transverse tensile strength TD of ≥20MPa, and an elongation at break of ≥88% (purchased from Kunshan Boyi Xincheng Polymer Materials Co., Ltd., model CPB1M80ST3).
[0079] 2. A preparation process of a diaphragm material, same as that of Example 1.
[0080] Example 3
[0081] 1. A diaphragm material, which is different from that in Example 1 in that:
[0082] The thickness of the release layer is 40 μm.
[0083] The coating thickness of the first thermoplastic elastomer layer was 10 μm.
[0084] The coating thickness of the second thermoplastic elastomer layer was 10 μm.
[0085] The thickness of the nano toughening layer is 10 μm.
[0086] 2. A preparation process of a diaphragm material, same as that of Example 1.
[0087] Comparative Example 1
[0088] 1. A diaphragm material, which is different from that in Example 1 in that:
[0089] The 100% modulus of the oily polyurethane resin is 8.0 MPa, the tensile strength is 65.0 MPa, and the elongation is 400%. (Purchased from Yantai Huada Chemical, model number MP-865PS).
[0090] 2. A preparation process of a diaphragm material, same as that of Example 1.
[0091] Comparative Example 2
[0092] 1. A diaphragm material, which is different from that in Example 1 in that:
[0093] The gradient temperature of the oven was set as follows: 60°C for 1 min; 90°C for 10 min; 100°C for 5 min; 110°C for 3 min; 95°C for 5 min; and 60°C for 10 min.
[0094] 2. A preparation process of a diaphragm material, same as that of Example 1.
[0095] Comparative Example 3
[0096] 1. A diaphragm material, which is different from that in Example 1 in that:
[0097] The coating speed is 30 m / min.
[0098] 2. A preparation process of a diaphragm material, same as that of Example 1.
[0099] Performance Testing
[0100] 1. Hardness: The samples obtained in the examples and comparative examples were tested according to the national standard GB / T 6739-1996 "Determination of Smear Hardness by Pencil".
[0101] 2. Temperature resistance: The samples obtained in the examples and comparative examples were placed at -190°C and 200°C for 4 hours, respectively, and the elongation (ISO 527-1BA) and tensile modulus (ISO 527-1BA) after treatment at different temperatures were measured.
[0102] The specific test results are shown in Table 1.
[0103] Table 1 Performance test results of examples and comparative examples
[0104]
Claims
1. A diaphragm material, characterized in that: From top to bottom, they are respectively a release layer, a first thermoplastic elastomer layer, a nano-toughening layer, and a second thermoplastic elastomer layer; The thermoplastic elastomer in the first thermoplastic elastomer layer is a polyurethane thermoplastic elastomer; The polyurethane thermoplastic elastomer is an oily polyurethane resin; The 100% modulus of the oily polyurethane resin is 5-15 MPa, the tensile strength is 30-60 MPa, and the elongation is 450-700%; The method for preparing the diaphragm material comprises the following steps: (1) dissolving the thermoplastic elastomer in the first thermoplastic elastomer layer in an organic solvent, stirring and filtering, and then adding isocyanate and continuing to stir and dissolve to obtain a raw material composition for the first thermoplastic elastomer layer; (2) coating the raw material composition of the first thermoplastic elastomer layer obtained in (1) on the release layer and placing it in an oven to dry; then heating and laminating it with the nano-toughening layer, and peeling off the nanofiber membrane base film material and rolling it up from the back; (3) coating the raw material composition of the first thermoplastic elastomer layer obtained in (1) on the release layer and placing it in an oven to dry; then heating and laminating it with the film obtained in (2), and peeling off the OPP film material of the composite film obtained in (2) and rolling it up from the back; (4) placing the film obtained in (3) under a certain temperature and humidity for aging to obtain; The temperature of the oven is set to a gradient temperature increase; the gradient temperature of the oven is set to: 50-65°C for 1-2 min; 65-80°C for 1-2 min; 80-95°C for 1-2 min; 95-105°C for 1-2 min; 105-115°C for 1-2 min; 80-90°C for 1-2 min; 55-65°C for 1-2 min; The coating method is selected from one of blade coating, roller coating, brush coating, spray coating, and cationic electrodeposition; the coating speed is 5-25 m / min.
2. A diaphragm material according to claim 1, characterized in that: The material of the release layer is selected from one of polyethylene terephthalate, co-extruded oriented polypropylene film, biaxially oriented polypropylene film, cast polypropylene film and release paper.
3. A diaphragm material according to claim 1 or 2, characterized in that: The material of the release layer is OPP film and / or CPP film; The CPP film has a peeling force of 1-100 g / 25 mm, a longitudinal tensile strength MD of ≥20 MPa, a transverse tensile strength TD of ≥15 MPa, and a breaking elongation of ≥80%.
4. A diaphragm material according to claim 1, characterized in that: The nano toughening layer is obtained by preparing a nanofiber membrane by using a thermoplastic polymer through an electrostatic spinning process; The thermoplastic polymer is selected from one or more of polyimide, polyamide, polycaprolactone, polyethersulfone, polyetherketone, polyolefin and polyphenylene ether.
5. The method for preparing a diaphragm material according to claim 4, characterized in that: The weight ratio of the thermoplastic elastomer to the organic solvent in the first thermoplastic elastomer layer is 1:(1.5-7); The solid content of the filtered thermoplastic elastomer is 7-55wt%.
Citation Information
Patent Citations
A loudspeaker
CN105188000B
Method for producing TPU thin film
CN106863833A
Method for interlayer toughening of carbon fiber prepreg through nano-particle polymer composite nano-fiber membrane
CN113002024A
Composite diaphragm, preparation method for composite diaphragm, and sound producing device
WO2022001015A1